Invisible Sensors: Simultaneous Sensing and Camouflaging in Multiphysical Fields. (26th October 2015) - Yang, Tianzhi; Bai, Xue; Gao, Dongliang; Wu, Linzhi; Li, Baowen; Thong, John T. L.; Qiu, Cheng‐Wei
Abstract : The first multiphysical invisible sensor is theoretically and experimentally presented. An ultrathin, homogeneous, and isotropic shell is designed to simultaneously manipulate heat flux and DC current and eliminate the multiphysical perturbation, while maintaining the receiving and transmitting properties of the sensor.